Application of a Cloud Video Conference Method for Recruiting Healthy Subjects Into an Early-Phase Clinical Trial During the COVID-19 Pandemic - Wang, Zejuan; Du, Aihua; Li, Min; Zang, Siqi; Liu, Xiaona; Zhang, Dan; Chen, Gang; Zhang, Lina; Zhang, Yanan; Wang, Jin (Frontiers in Public Health, 2021)
Objective: Our objective is to explore the effect of applying cloud video conferencing methods to the informed consent process in an early-phase clinical trial during the COVID-19 pandemic. Methods: All participants who intended to participate in the trial were informed via a cloud video conference before signing the informed consent forms (ICF). Then, the attitudes of the participants with the cloud video conference and their understanding of the trial were evaluated using a questionnaire when they visited to sign the ICF onsite. Results: A total of 165 subjects participated in the cloud video conference process, and 142 visited the site to sign and date the ICFs at the center during the appointment time. The survey showed that nearly 100% of the subjects evaluated the video-based informed consent process as very good or good and gave correct answers to questions about the trial. Furthermore, 136 (95.8%) subjects believed that the knowledge about the trial derived via the video-based informed consent process was consistent with the onsite reality, and 139 (97.9%) subjects expressed their willingness to participate in an informed consent procedure undertaken through an online video conference. Conclusions: The video-based informed consent process achieved the same effects as an onsite informed consent process. The former saves time and cost of transportation for the subject and exhibits good public acceptance; especially in light of the COVID-19 pandemic, this process is conducive for reducing the risk of subject infection due to travel and would also help avoid crowding on site.